Optimizing IT Project Management: Leveraging Jira Automation for IT implementations - Andreea-Izabela BOSTAN (Communications of International Proceedings, 2024)
In the dynamic landscape of Information Technology (IT) Project Management, the efficient utilization of resources and the timely execution of tasks are critical for successful project outcomes. The objective of this study is to explore the application of Robotic Process Automation (RPA) in the realm of IT project management, specifically focusing on leveraging Jira automation for software implementations. By automating repetitive tasks and workflows within the Jira platform, IT teams can streamline processes, reduce manual intervention, and enhance productivity. This study is relevant as it investigates implementation strategies associated with integrating RPA into Jira for IT project management. Drawing from industry insights on how methodologies are applied for project development, the research underscores the potential of Jira automation in optimizing the project workflows. Additionally, several scenarios, potential automation candidates, are discussed, and automated workflows are suggested in order to improve team collaboration and accelerate project delivery. Ultimately, this article aims to enhance efficiency and effectiveness in IT project management through the strategic deployment of Jira automation powered by RPA technologies.
Keywords: Robotic Process Automation; Intelligent Automation; Project management; UiPath; Jira